Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak" Quercus suber L." - Aranda, I; Simón, J Puértolas (Investigación agraria. Sistemas y recursos forestales, 2008)
The current ongoing increase in the atmospheric CO2 concentration is an unquestionable fact. Thus, plants are bound to live in a more enriched CO2 world in a not far-off future. In this new framework, regeneration of forest tree species may be modified as a consequence of the change in the current patterns of seedling response to other environmental resources, such as water or light. We studied the impact of an elevated CO2 concentration on the interaction of drought and light upon the water relations of cork oak (Quercus suber L.) seedlings. In a complete factorial design of contrasting light (HL vs LL), water (WW vs S) and CO2 levels (800 ppm vs 370 ppm), we analysed the influence of each factor and its interaction in the modification of different leaf water parameters in potted seedlings after a 6 months experimental period. These parameters were derived from the construction, with leaf materials, of the P-V curves: osmotic potential at full turgor (Ψπ100), osmotic potential at zero turgor (Ψπ0), modulus of elasticity at full turgor (εmax), and the ratio dry/turgor weight (DW/TW). Doubling of the CO2 levels over the current concentration (380 ppm) did not change any of the studied leaf water parameters, while light and water availabilities had a significant influence. This result does not exclude changes in other basic physiological parameters that could modify the pattern of cork oak regeneration responding to a CO2 enriched atmosphere in the future, and under climatic conditions different to the current ones
Keywords: CO2 enrichment; Cork oak; PV curves; shade; Water availability